Volume Oksigen Maksimal (Vo2 Max) Mahasiswa Program Studi Pendidikan Kepelatihan Olahraga Universitas Gunung Leuser Aceh - Afrizal, Afrizal (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The aim of this research is to determine the VO2 max level of students in the sports coaching education study program at Gunung Leuser University, Aceh, Academic Year 2023/2024. This research is a descriptive research. Data collection uses a survey method with tests and measurements. The instrument used to measure the VO2 max test uses the Bleep Test. The subjects in this research were students from the sports coaching education study program at Gunung Leuser University, Aceh, Academic Year 2023/2024. 117 students consisted of men and women. The data analysis technique used in this research is quantitative descriptive analysis expressed in percentage form. The conclusions that can be drawn from this research are the VO2 max of male and female students as follows: in the very good category there were 5 students (4.3%), good for 11 students (9.4%), fair for 45 students (38.4%). %), less than 24 students (20.5%) and very less than 32 students (27.4%). Keywords: VO2MAX, Students Sports Coaching Education Study Program